Determinants and consequences of voluntary switches to Chinese auditors in Hong Kong. Issue 3 (December 2019) - Liu, Zhenfeng; Lin, Stephen
Abstract: Hong Kong market regulators have permitted 12 large Chinese accounting firms to audit the financial statements of Chinese firms that cross list in Hong Kong (i.e., H-share firms) since 2010. This paper examines the characteristics of H-share firms that voluntarily replaced their Hong Kong (HK) auditors with Chinese auditors, and the market reaction to auditor switches following this policy. We find that 38 out of 147 H-share firms voluntarily switched to Chinese auditors during 2011–2013. Switching firms are larger in size and are less likely to use Big4; they also have less need for external financing, a longer cross listing history, and a lower percentage of foreign revenue. We also find that investors negatively react to the auditor switches from HK non-Big4 to China non-Big4, but do not react to the auditor switches from HK Big4 to China Big4. This suggests that investors perceived lower audit quality for China non-Big4.